The crow - Pope, Tim, 1956-; Perez, Vincent, 1964-; Kirshner, Mia, 1976-; Brooks, Richard, 1962-; Pop, Iggy, 1947- (Bad Bird Productions, 1996)
Ενας νεκρός αναδύεται από τον άλλο κόσμο και με οδηγό ένα κοράκι εκδικείται τους δολοφόνους του.